Analisis Pengaruh Likuiditas Dan Solvabilitas Terhadap Rentabilitas Pada Koperasi Karyawan PLN Cipta Usaha - Supriadi, Yoyon; Sofyana, Astie (Sekolah Tinggi Ilmu Ekonomi Kesatuan, 2012)
Each company must set up to achieve a certain goal, in both the short and long term. Generally short-term corporate goal is to achieve maximum profit, while the long-term goal is to maximize firm value. In maximizing this value, the balance between liquidity, solvency and rentability should always be considered. Liquidity is the ability of the company to meet its obligations to be immediately due. Solvency is the ability companies to meet all obligations when the company declared bankrupt or liquidated with all its assets. While rentability is the companies abilitiy to generate profit. In this case, will be discussed on an analysis to the influence of the ability of UKM s in meeting short-term liabilities and long-term with assets owned and the ability to obtain profits with the liquidity it has. The purpose of this discussion is to find liquidity in the cooperative, the cooperative solvency, rentability in the cooperative and the influenceof liquidity to solvency and rentability on the emplooyes PLN Business Notice. The result of the discussion on the Cooperative Employees PLN Copyright Business shows that liquidity analysis on EUR Notice Employees Cooperative Enterprises each year has decreased drastically over the 4 (four) years, but increased again in the fifth year but the increase was not significant to the solvency analysis of the Cooperative Employees Business Notice PLN annually increased and decreased. For the analysis of rentability at PLN Notice Employees Cooperative Enterprise, the calculation of ROA (Return on Asset) increase and decrease each year, while for calculation of ROE (Return on Equity) is the same with the calculation of ROA that each year has increased and decreased. Evaluation results shows that analysis of the effect of liquidity on the solvency and rentability suggest that liquidity has a very strong relationship with the solvency and rentability, a significant effect of liquidity to solvency and rentability is not good. Moreover, judging from Fhitung, the effect of liquidity on the solvency and rentability have not connection between the two because the value Fhitung is greater than Ftabel . similarly, viewed from thitung the influence of liquidity to solvency and rentability have no significant effect because thitung smaller than ttabel.